Intestinal-pulmonary axis: a ‘Force For Good’ against respiratory viral infections - Zhu, Jianing; Huang, Zihang; Lin, Ying; Zhu, Wenxu; Zeng, Binbin; Tang, Dong (Frontiers in Immunology, 2025)
Respiratory viral infections are a major global public health concern, and current antiviral therapies still have limitations. In recent years, research has revealed significant similarities between the immune systems of the gut and lungs, which interact through the complex physiological network known as the “gut-lung axis.” As one of the largest immune organs, the gut, along with the lungs, forms an inter-organ immune network, with strong parallels in innate immune mechanisms, such as the activation of pattern recognition receptors (PRRs). Furthermore, the gut microbiota influences antiviral immune responses in the lungs through mechanisms such as systemic transport of gut microbiota-derived metabolites, immune cell migration, and cytokine regulation. Studies have shown that gut dysbiosis can exacerbate the severity of respiratory infections and may impact the efficacy of antiviral therapies. This review discusses the synergistic role of the gut-lung axis in antiviral immunity against respiratory viruses and explores potential strategies for modulating the gut microbiota to mitigate respiratory viral infections. Future research should focus on the immune mechanisms of the gut-lung axis to drive the development of novel clinical treatment strategies.